The Last WAVE: Integrating with Mininet for More Flexible and Reproducible Network Experiments - Souza, Ivalcleb L. Benigno de; Maciel Jr., Paulo Ditarso; Almeida, Leandro C. de (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2026: Anais Estendidos do XLIV Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2026.22871, 2026)
Experimentation is essential in computer network research because it enables controlled and reproducible evaluation of applications and protocols. This paper presents the third version of WAVE (Workload Assay for Verified Experiments), evolving from the original multiple-workload generator and its later extensions with new load models and microburst support. WAVE controls the execution of real application instances over time according to mathematical workload models, currently supporting sinusoid, flashcrowd, and step patterns, as well as video-oriented workloads and microbursts. The main contribution of this version is the native integration with Mininet, which removes the previous integration barrier with simulated environments and allows workload generation and network emulation to be configured in a unified workflow. In this integrated setting, researchers can define different topologies, such as linear and tree, and inject realistic network parameters, including additional delay and packet loss. These capabilities provide a more flexible and reproducible environment for evaluating distributed applications and network behavior under diverse experimental conditions.